A Comparative Study About Cost of the Pilgrimage Characteristics-Based Rupiah and Dinar (Survey on Pt. Bank Syariah Mandiri Branch Bandung and Dinar Tauhid Bandung) - Firmansyah Firmansyah (UIN Sunan Gunung Djati Bandung, 2013)
Hajj is obligatory for Muslims who are able, physically, mentally, and materially. Trend of pilgrims making the Hajj pilgrimage from year to year increase. Due to capacity limitations in Mecca that makes every country of the quota number of people who can perform the pilgrimage every year. Because currencies are pilgrims Indonesia Rupiah (paper money not based on gold / fiat money), then the Hajj planning to use the money amount in at least two uncertainties, the factors of inflation and exchange rate factors (exchange rate). Because these two factors the cost of the pilgrimage (ONH) has a tendency to increase every year, up from year to year. increases in the cost of the pilgrimage can be a very significant amount. To fulfill the ONH is one way to save money both in rupiah in PT. Bank Syariah Mandiri Branch Bandung or even saving dinar (4.25 grams of 22 carat gold) in Dinar Tauhid Bandung. This study aims to determine the operating system cost of the pilgrimage rupiah based in PT. Bank Syariah Mandiri, operating system cost of pilgrimage Dinar based in Dinar Tauhid Bandung, and the comparison of operating system-based cost of pilgrimage rupiah in PT. Bank Syariah Mandiri with dinar based in the Dinar Tauhid Bandung. Object of research is only one ONH, with different places, there are PT. Bank Syariah Mandiri branch of Bandung and Dinar Tauhid Bandung. In this study, use of comparative research methods. With the type of research is a qualitative study consisting of a definition of Haj savings and the savings contract is used, the mechanism of how to save money, and profit sharing. Primary data obtained from interviews with relevant parties, while the secondary data obtained from books, journals, internet and other literature.Based on the results of research that has been done shows that saving money dinar with the product more profitable m-dinar is free of ONH price inflation rise to an average of 11.21% per year, and the dinar appreciated on average toward the rupiah currency (fiat money) by 26,46% per year. Saving dinar get favorable share outcome.